NEP 2020 and Sustainable Development of Education in India: A Comprehensive Review - Upadhye, Shashikant Sudarshan (AG Volumes, 2025)
When the Indian government unveiled "the National Education Policy (NEP) 2020", almost every segment of society welcomed the announcement. After 1986, the education policy underwent a significant shift. Because of this, everyone saw this government decision as an optimistic and constructive move that not only signals a significant shift in the area of education but was also deemed suitable to address the difficulties posed by the present global educational system. In this study, review the various literature’s work on NEP and sustainable development of Indian education. It concluded that the NEP 2020 marks a transformative shift in India’s education system, aiming to empower students with knowledge, skills, and human values essential for addressing present and future societal challenges. By integrating digitalization, vocational education, interdisciplinary learning, and emerging technologies such as AI, 3D printing, and biotechnology, the policy enhances employability and fosters innovation. NEP 2020 also promotes flexibility in curriculum, multilingualism, and continuous assessment reforms, ensuring a holistic and skill-based learning approach.